Efficacy of different botanical and chemical insecticides against rice hispa (Dicladispa armigera) - Roy, P; Uddin, MM; Islam, KS; Das, KR (Progressive Agriculture, 2017)
An experiment was carried out in the Entomology Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh to determine the efficacy of six botanicals and four chemical insecticides for controlling rice hispa, Dicladispa armigera during the period of July to December 2013. In conducting the experiment BR11 rice variety was selected where ten treatments namely six botanicals such as Neem oil, Mahogany oil, Mixture of Neem and Mahogany oil, Bishkatali leaf extract, Pitraj leaf extract and Mixture of Bishkatali and Pitraj leaf extract and four chemical insecticides Sevin85SP, Advantage20EC, Cup50EC, Kinalux 25EC were laid out in the Randomized Complete Block Design (RCBD). Overall leaf infestation by rice hispa and infestation by adults and grubs separately were recorded at different time intervals. In addition to these, overall effect of pest infestation on the grain yield of rice was also examined. Among the six botanicals, Neem oil was most effective in controlling rice hispa, as overall leaf infestation was 21.20% and the infestation by adults and grubs were 14.43% and12.57%. On the other hand, among chemical insecticides, maximum efficacy was found under the treatment of Sevin 85SP where minimum leaf infestation was 9.22%, infestation by adults and grubs were 5.88% and 5.00% respectively. In case of yield, Sevin 85SP (4.62 ton/ha) showed the best efficacy in comparison to other treatments. Therefore, application of Sevin 85SP (3.46ml/L) and Neem oil (2ml/100ml) were examined as the best options in controlling rice hispa. So, it could be recommended to use Sevin 85 SP and Neem oil for the management of rice hispa. Progressive Agriculture 28 (2): 64-72, 2017